A self-cascaded unimolecular prodrug for pH-responsive chemotherapy and tumor-detained photodynamic-immunotherapy of triple-negative breast cancer. (January 2023) - Yao, Defan; Wang, Yanshu; Bian, Kexin; Zhang, Bingbo; Wang, Dengbin
Abstract: Despite the success of immune checkpoint blockade (ICB) therapy in cancer management, ICB-based immunotherapy of triple-negative breast cancer (TNBC) still suffers from immunosuppressive tumor microenvironment (ITM). To break through the bottleneck of TNBC immunotherapy, a self-cascaded unimolecular prodrug consisting of an acidic pH-activatable doxorubicin and an aggregation-induced emission luminogen (AIEgen) photosensitizer coupled to a caspase-3-responsive peptide was engineered. The generated prodrug, could not only release doxorubicin initiatively in acidic tumor microenvironment, but also activate apoptosis-related caspase-3. The activated caspase-3 could in turn trigger release and in situ aggregation of photosensitizers. Importantly, the unimolecular prodrug exhibits a renal clearance pathway similar to small molecules in vivo, while the aggregated AIEgens prolong tumor retention for long-term fluorescence imaging and repeatable photodynamic therapy (PDT) by only one single-dose injection. Furthermore, the tumor-detained PDT boosts both immunogenic cell death of TNBC cells and maturation of dendritic cells. Finally, the combination of repeatable PDT with ICB therapy further promotes the proliferation and intratumoral infiltration of cytotoxic T lymphocytes, and effectively suppresses tumor growth and pulmonary metastasis. This prodrug is a proof-of-concept that confirms the first self-cascaded chemo-PDT strategy to reverse the ITM and boost the ICB-mediated TNBC immunotherapy.